2007
DOI: 10.1021/om061107j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of HC[(CBut)(NAr)]2Al (Ar = 2,6-Pri2C6H3) and Its Reaction with Isocyanides, a Bulky Azide, and H2O

Abstract: The reaction of H2C[(CBu t )2(NAr)2] (Ar = 2,6-Pr i 2C6H3) with AlEt3 in refluxing toluene gave HC[(CBu t )2(NAr)2]AlEt2 (1) in high yield. Treatment of 1 with 2 equiv of iodine in toluene yielded HC[(CBu t )2(NAr)2]AlI2 (2). Reduction of 2 with potassium resulted in the formation of the tert-butyl-substituted β-diketiminato aluminum(I) compound HC[(CBu t )2(NAr)2]Al (3). Reactions of 3 with isocyanides, H2O, and a bulky terphenyl azide were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 41 publications
3
65
0
3
Order By: Relevance
“…However, no reports have described the CN bond cleavage of β‐diketiminato complexes induced by NHCs. The mechanism might be similar to that reported by us for the reaction of 1 with the isocyanide, CNAr 8. Notably, NHC‐stabilized group‐13 species having multiple bonding are only confined to those containing a BB bond 15…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…However, no reports have described the CN bond cleavage of β‐diketiminato complexes induced by NHCs. The mechanism might be similar to that reported by us for the reaction of 1 with the isocyanide, CNAr 8. Notably, NHC‐stabilized group‐13 species having multiple bonding are only confined to those containing a BB bond 15…”
Section: Methodssupporting
confidence: 76%
“…Since the isolation of the first β‐diketiminato monovalent aluminum compound [Al{HC[(CMe) 2 (NAr) 2 ]}] ( 1′ ) by Roesky and co‐workers, its reactivity has been extensively investigated 6. 7 Very recently, we reported the synthesis of Al I monomer 1 (Scheme ), which contains larger groups, that is, tert ‐butyl groups, on the β position of the ligand backbone, and its CN bond cleavage reaction with an isocyanide 8. The results prompted us to examine reactions of 1 with other Lewis bases, especially those that are isoelectronic with isocyanides, such as NHCs, for the understanding of the reaction mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…5). 59,60 This clearly demonstrates the role played by ancillary ligands coordination in destabilizing the Al(I) species and triggering BDI degradation. 55 This phenomenon appears to be promoted by the coordination of sigma donors, which destabilize the low-valent metal species.…”
Section: Reductive Cleavagementioning
confidence: 79%
“…The most striking feature of this structure, shown on Fig. 59,296 Similarly, our group isolated a metallacyclobutane amido species from the reaction of (MAD)Nb(vNar)(N t Bu)(OEt 2 ) with t BuN 3 , the formation of which is explained by a two-step process involving (a) nitrene transfer and reformation of an dissymmetric BDI ligand leading the Nb(III) imido (BDI (Dipp,tBu),Me )Nb (NDipp) intermediate species (see section 4) and (b) imidomediated C-H bond activation of the t Bu group from the asymmetric BDI ligand (Scheme 84bottom). 292 Note that upon substitution by arylchloride groups, intramolecular ortho chlorine coordination appears to be necessary to stabilize the cationic molybdenum imido alkylidene species (Scheme 82).…”
Section: Fig 24mentioning
confidence: 86%
“…In 2004, Roesky et al. reported that NacNacAl: 1 (NacNac=HC(CMeNAr) 2 − and Ar=2,6‐ i Pr 2 C 6 H 3 ), readily activates the P−P bond of white phosphorus P 4 and the S−S bond in elemental sulfur S 8 ,. Recently, Schulz et al.…”
Section: Methodsmentioning
confidence: 99%